The Influence of Student Inquiry and Curiosity Level on The Learning Outcomes of The Cognitive Aspects of History of Islamic Culture Subject - U Abdullah Mu'min; Budi Munawar Khutomi; Herri Azhari (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aimed to find the influence of the inquiry approach and students’ curiosity on the learning outcomes of cognitive aspects on History of Islamic Culture subject. This research was conducted at MTs Jamiyatul Aulad Palabuhanratu Sukabumi Regency. This research approach was quantitative with the quasi experiment and treatment by level 2 X 2. The number of students who became the samples of the study was 64 students, divided into two groups, each consisting of 32 students. Data analysis techniques were two-path analysis of variance (ANOVA) followed by Tukey test. The results of this study indicated that 1) learning outcomes of the students taught using the inquiry method were higher than those taught using conventional method, 2) there was an influence of interaction between the inquiry method and the level of curiosity on students’ learning outcomes, 3) learning outcomes of students with high curiosity level treated by inquiry method were higher than students with high curiosity levels given conventional method; and 4) learning outcomes of students with low curiosity levels were higher than students with low curiosity levels given a conventional method.